Local Sport Event Policies and Sustainability: A Puzzle Approach - Jensen, Christian Tolstrup (Frontiers in Sports and Active Living, 2021)
As demands for more sustainable ways of living increase, organisers of sport and other events have come under increasing pressure to adapt. At the same time, more and more national and local event policies increase the local demand for events. These two trends raise the question on how policy makers solve the puzzle of combining the demand for events with a sustainable way of living. This relation between event policies and sustainability has so far been subject to little research. The present paper analyses the conceptualisation of sustainability in all local policies relating to events in Norwegian municipalities. The material covered both local master plans and more specific policies on events. The paper is based on the analysis of policies covering 22 municipalities. Its document analysis shows that all of the municipalities had adopted a “broad” conceptualisation of sustainability, i.e. pursued a development, which should not limit the possibilities of future generations, in their general development plans. Although these plans also serve as a basis for every other policy, the paper also shows that the municipalities in the specific policies for events often had “narrow” conceptualisation of sustainability, i.e. focusing on making the event reoccurring and increasing the local capacity for events. These findings emphasise the relevance of looking at the local level when conducting future studies on events and sustainability and suggest that the practitioners acknowledge the complexity of the question as a first step to solve the puzzle.